1986
DOI: 10.1007/bf00237470
|View full text |Cite
|
Sign up to set email alerts
|

Transneuronal transport of peroxidase-conjugated wheat germ agglutinin (WGA-HRP) from the olfactory epithelium to the brain of the adult rat

Abstract: The sensory neurons of the olfactory epithelium, as a consequence of their odor detection function, contact both the external environment and the central nervous system. The possibility that substances applied to the epithelium might reach the central nervous system was investigated by the intranasal application of peroxidase-conjugated wheat germ agglutinin (WGA-HRP). WGA-HRP was transported through olfactory receptor axons to the glomerulus of the olfactory bulb. Reaction product was localized electron micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(78 citation statements)
references
References 50 publications
3
73
0
2
Order By: Relevance
“…However, the mechanism by which the D1-D2 interfering peptide is transported to the CNS and PFC remains unknown. It is likely that the D1-D2 interfering peptide is being transported to the CNS via extracellular mechanisms, as the POD device preferentially deposits substances on the olfactory epithelium (Hoekman and Ho, 2011a,b), relatively short time is required for transport to the PFC (Figure 3), and previous studies demonstrate that peptides of this type are transported to the CNS via extracellular mechanisms (Baker and Spencer, 1986;Jansson and Bjork, 2002;Yang et al, 2013). A recent study by Yang et al (2013) showed that for a 22-amino acid, TAT-linked membrane-permeable peptide similar in size to the D1-D2 interfering peptide, an IN dose of only 7% that of the IV dose previously administered (Nijboer et al, 2008) was able to alleviate hypoxia-induced ischemic brain injury in a rat preclinical model.…”
Section: Discussionmentioning
confidence: 93%
“…However, the mechanism by which the D1-D2 interfering peptide is transported to the CNS and PFC remains unknown. It is likely that the D1-D2 interfering peptide is being transported to the CNS via extracellular mechanisms, as the POD device preferentially deposits substances on the olfactory epithelium (Hoekman and Ho, 2011a,b), relatively short time is required for transport to the PFC (Figure 3), and previous studies demonstrate that peptides of this type are transported to the CNS via extracellular mechanisms (Baker and Spencer, 1986;Jansson and Bjork, 2002;Yang et al, 2013). A recent study by Yang et al (2013) showed that for a 22-amino acid, TAT-linked membrane-permeable peptide similar in size to the D1-D2 interfering peptide, an IN dose of only 7% that of the IV dose previously administered (Nijboer et al, 2008) was able to alleviate hypoxia-induced ischemic brain injury in a rat preclinical model.…”
Section: Discussionmentioning
confidence: 93%
“…The xenobiotic is then transported within the cell via slow or rapid transport systems to the transmost saccule of the Golgi apparatus, where it is packaged into vesicles bound for axonal terminals. 33 Usually there is minimal involvement of glial cells, implying limited release into the extracellular space. 15 Agents that are not synaptically transported but yet enter the cell, such as leucine and horseradish peroxidase, are taken up by bulk endocytosis and processed into protein components of the cell, not the Golgi saccule.…”
Section: Evidence That Xenobiotics Can Enter the Brain Via The Olfactmentioning
confidence: 99%
“…Two or 3 weeks after the operation, the animals were anesthetized with pentobarbital and placed on their backs. For anterograde labeling of the olfactory nerve, 100 l of 1% wheat germ agglutinin-horseradish peroxidase conjugate (WGA-HRP) in PBS was injected slowly into nasal cavity (41). After 24 h, the animals were re-anesthetized and perfused with 4% paraformaldehyde/ PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Following olfactory nerve axotomy, SM-216289 was locally and continuously administered between the cribriform plate and the olfactory bulb of operated animals at the rate of 6 g/6 l/day through a cannula using osmotic pumps. Two or 3 weeks after the axotomy, olfactory nerves were anterogradely labeled with wheat germ agglutinin-horseradish peroxidase conjugate (WGA-HRP) (41), and the length of regenerated olfactory nerve was determined by the methods described under "Experimental Procedures" (Fig. 5A).…”
Section: Sm-216289 Inhibits Binding Of Sema3a To Neuropilin-1-inmentioning
confidence: 99%